Estrategic management during the transicion period to optimise productivity and reproductive performance in the dairy herd (2009)
In dairy herds, the interval between calving and pregnancy depend on many factors including preparation of the cow for calving, dietary management before and after calving. Factors such as hypocalcemia and body condition are determinant in the presentation of postpartum pathologies and ovarian activity resumption. Additionally, management of the dairy cattle should include fixed time artificial insemination protocols to increase the number of animals bred close to the voluntary waiting period and pregnancy rates. The following review will address topics related with cattle body condition and puerperal hypocalcemia that affect negatively postpartum reproductive performance and also will, address management alternatives to improve pregnancy rates y to reduce days open.